PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Dharma, Nyoman Budhi Setya; Noviari, Naniek (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
This study aims to examine and provide empirical evidence of the influence of corporate social responsibility (CSR) and capital intensity against tax avoidance. The independent variable of this research was CSR and capital intensity, the dependent variable is tax avoidance. The independent variables CSR is measured by CSR disclosure GRI indicators G3.1. Variable capital intensity was measured using the intensity ratio of fixed assets. The dependent variable tax avoidance measured by effective tax rate (ETR). The population was 144 companies listed on the Stock Exchange in 2012-2015. Samples were selected using purposive random sampling method with certain criteria and obtained as many as 28 companies that meet the criteria. Data analysis technique used is multiple regression analysis. Regression analysis showed that the variables of CSR and the capital intensity of each negative and positive impact on tax avoidance.
Keywords: Corporate Social Responsibility (CSR), Capital Intensity, Tax Avoidance